2021
DOI: 10.1161/jaha.120.019843
|View full text |Cite
|
Sign up to set email alerts
|

Right Heart Catheterization in Cardiogenic Shock Is Associated With Improved Outcomes: Insights From the Nationwide Readmissions Database

Abstract: Background The usefulness of right heart catherization (RHC) has long been debated, and thus, we aimed to study the real‐world impact of the use of RHC in cardiogenic shock. Methods and Results In the Nationwide Readmissions Database using International Classification of Diseases, Tenth Revision ( ICD‐1 0 ), we identified 236 156 patient hospitalizations with cardiogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 21 publications
1
36
0
2
Order By: Relevance
“…when PA pressures are obtained (22). In addition, Ranka et al presented a validated real-world analysis, although not randomized (23).…”
Section: Discussionmentioning
confidence: 99%
“…when PA pressures are obtained (22). In addition, Ranka et al presented a validated real-world analysis, although not randomized (23).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive assessment with a Swan-Ganz (or similar) catheter represents a valuable tool in patients with undefined haemodynamics. 44 , 45 Arrhythmias, including atrial fibrillation, are commonly found in severe CRS. 27 , 34 Treatment should be according to current guidelines, including optimization of serum electrolytes, antiarrhythmic therapy (e.g.…”
Section: Cardiovascular Adverse Eventsmentioning
confidence: 99%
“…Although historical studies such as ESCAPE (Evaluation Study of Congestive heart failure And Pulmonary artery catheterization Effectiveness) suggested limited utility and possible harm with the use of PAC, many, including ESCAPE, actively excluded patients with CS [ 18 ]. More recently, observational studies of large cohorts have revealed that PAC in CS is associated with more aggressive therapy [ 19 , 20 ] and improved survival [ 20 , 21 ]. PAC as a diagnostic tool can lend greater precision to hemodynamic profiling and contribute to expediting decision-making and rapid stabilization, all of which contribute to improved clinical outcomes.…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…Congestion, a central factor contributing to poor outcomes in HF-CS, may persist despite adequate circulatory support with MCS and vasoactive therapies [ 12 , 20 ]. Acute kidney injury (AKI) in this setting is not uncommon, and is associated with poor outcomes [ 3 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%